Pengaruh E-Service Quality dan Kepuasan Nasabah terhadap Loyalitas Nasabah dalam Menggunakan Livin by Mandiri - Divana Putri Tiva Alovani Simangunsong; Dedi Purwana; Ayatulloh Michael Musyaffi (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
The development of technology in the industrial era 5.0 has brought significant changes in various sectors, including banking. Banking digitalization, especially through mobile banking services such as Livin' by Mandiri, provides easy, fast and efficient transactions, which have an impact on customer satisfaction and loyalty. This study aims to analyze the effect of e-service quality and customer satisfaction on customer loyalty of Livin' by Mandiri. Using a quantitative approach and Partial Least Squares (PLS) analysis method, this study collected data from 400 respondents through an online questionnaire. The results showed that e-service quality has a positive effect on customer loyalty, especially among young customers (17-25 years old) who use the application for educational purposes and daily transactions. In addition, customer satisfaction also has a positive effect on customer loyalty, with the majority of respondents feeling satisfied with the ease and efficiency of the services provided. These findings demonstrate the importance of e-service quality and customer satisfaction in building customer loyalty in the digital era. This study contributes to the understanding of the factors that influence customer loyalty in the context of digital banking services in Indonesia.